Behavior of reinforced concrete beams strengthened using CFRP sheets with superior anchorage devices - Zaki, Mohammed Ameen (Kansas State University, 2018)
The use of carbon fiber reinforced polymer (CFRP) anchors can improve the performance of reinforced concrete (RC) beams strengthened in flexure with CFRP sheets. This improvement results from delaying or controlling the debonding of FRP sheets at failure. In this research, six full-scale T beams and six full-scale rectangular beams are prepared and tested as two separate series. All the specimens are strengthened identically using three layers of unidirectional CFRP sheets and one layer of bidirectional CFRP sheet. The first strengthened beam in each series is anchored with side GFRP bars inserted longitudinally to both sides of the beam. The second strengthened beam in each series is anchored with GFRP patches applied to both sides of the beam. CFRP spike anchors are utilized for the other beams in the two series. The third beam in each series is secured with CFRP spike anchors of 16 mm diameter at 140 mm spacing along the shear span. The fourth strengthened beam in each series is anchored with CFRP spike anchors of 19 mm diameter at 203 mm spacing along the shear span. Four CFRP anchors are applied to each shear span of the fifth beam in each series with 16 mm- diameter (spaced at 406 mm) to secure the flexural CFRP sheets. An end CFRP anchorage technique is considered for the last beam in each series, which includes installing one CFRP spike anchor placed at 76 mm from the free edge of CFRP sheets. The beams were tested under four-point bending until failure and the results for each series are evaluated. In addition, the outcome is compared with other anchorage techniques that have been examined by some researchers utilizing the same beam geometry and properties. The experimental testing and nonlinear analysis showed improvement in the flexural performance of anchored beams compared with those strengthened beams without anchorage. By attaining debonding or rupture failure modes for the T beams and concrete crushing failure mode for the rectangular specimens, the ultimate sectional force capacity is achieved. Accordingly, the results prove that the anchors offer an effective solution against premature debonding failure.
Keywords: flexural strengthening; CFRP spike anchorsCFRP sheets; anchorage devices